A systems-approach to modeling the EMS exchange-rate mechanism - Bewley, R; Kearney, C (Economic & Social Studies, 1989)
This paper examines the extent to which the EMS has succeeded in stablising intra-European exchange rates from external influences. It generalises earlier results by developing a systems approach to the problem which enables intra-currency volatility to be separated from the impact of external exchange rate shocks on the system as a whole. It is found that the EMS has indeed been successful in the intra-system task while the external effects on the entire system have increased.
Keywords: European economics; European Monetary System; EMS